Professional Self-Esteem as a Mediator Between the Perception of Teaching as a Profession and the Motivation to Study Teacher Education in an ODL Context - Nguéhan, Siméon Boris; Mukama, Evode (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2025)
This study investigates the mediating role of professional self-esteem in the relationship between motivation to pursue teacher education in an open distance learning (ODL) context and individuals’ perceptions of the teaching profession. Four hypothesises have been examined: 1) the perception of teaching as a profession has a positive effect on professional self-esteem; 2) professional self-esteem is positively related to the motivation to study teacher education in an ODL context; 3) the perception of teaching as a profession indirectly induces a motivation to study teacher education in an ODL context; and 4) the perception of teaching as a profession has a direct effect on motivation to study teacher education in an ODL context. Using a quantitative approach and adopting a cross-sectional research design, 314 respondents enrolled in an ODL programme in the two Cameroon anglophone state universities were sampled to unravel the complex dynamics underpinning critical variables. The findings revealed that professional self-esteem does indeed mediate the relationship between motivation to study teacher education through ODL and the perception of teaching. Moreover, teachers who perceive teaching as a respected and rewarding profession tend to have higher levels of professional self-esteem, which in turn increases their intrinsic motivation to study. Conversely, those with lower perceptions of the profession show reduced motivation, even when they recognise the convenience of the ODL system. Recommendations of the study include targeted interventions by educational institutions to promote teaching as a career by integrating strategies that build professional confidence among student teachers.